Tension tests on bored instrumented piles installed in marine Eocene clay. Issue 1 (April 2021) - Knudsen, J; Sorensen, K K; Steenfelt, J S; Trankjær, H
Abstract: This paper presents parts of the results from two full-scale loading tests (tension) on bored cast-in-place piles installed in high plasticity marine Eocene clay at a test site in Hinge, central Jutland, Denmark. Testing was carried out to investigate the development and distribution of shaft resistance on the test piles. Each test pile was instrumented with distributed fiber-optic strain and temperature cables, in addition to traditional vibrating wire strain gauges and tell tales. Selected examples of retrieved data are presented. The measured shaft resistance is compared to an analytical method based on the Danish National Annex to Eurocode 7, part 1 which represents a conservative estimate for the shaft resistance of bored piles. The results from the two full-scale loading tests (tension) on bored cast-in-place piles in marine Eocene clay show that the Danish code-requirement, concerning shaft resistance, is too conservative.